Socioeconomic status and adolescents’ risk-taking behavior: No longitudinal link or differences by neurobiological activation when anticipating social rewards - Armstrong-Carter, Emma; Kwon, Seh-Joo; Jorgensen, Nathan A.; Prinstein, Mitchell J.; Lindquist, Kristen A.; Telzer, Eva H. (Developmental cognitive neuroscience, 2025)
This longitudinal, preregistered study investigated the hypothesis that adolescents who are raised in socioeconomic adversity engage in relatively more health-compromising risk-taking behavior during years when they show relatively heightened anticipation to social rewards. We operationalized this on a neurobiological level as activity of the ventral striatum, a region of the brain that is involved in social reward processing. A sample of 170 racially and socioeconomically diverse adolescents (12years at Wave 1, 53 % women, 35 % Latine, 29 % White, 22 % Black) completed annual assessments for up to five years, yielding 478 total observations. During annual fMRI scans, adolescents completed a Social Incentive Delay task during which we measured activation of the ventral striatum in response to anticipating social rewards relative to social punishments. Adolescents also self-reported risk-taking behavior annually, and we linked measures of baseline socioeconomic status via parent report and neighborhood census data. Our preregistered hypotheses were not supported; baseline socioeconomic status was not associated significantly with risk-taking behavior, even during years when adolescents were more attuned to social rewards. Sensitivity analyses examined the role of the anterior insula and amygdala and also yielded null results. Adolescents’ risk-taking behavior may not be as closely linked to socioeconomic status or social reward activation as previously hypothesized.